Biodegradable quadripolymer foamed plastic and preparation method thereof
By using a combination of carbon dioxide-based polyester-polycarbonate tetracopolymer and n-pentane or isopentane, biodegradable foaming is prepared by using the press-pressure foaming method, which solves the problems of low foaming ratio, high cost and poor dimensional stability of existing materials, and achieves high foaming ratio and good mechanical properties.
Patent Information
- Application Number
- CN202510148258.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-02-11
AI Technical Summary
The existing biodegradable foam materials have low foaming ratio, high cost, poor dimensional stability and insufficient resilience, which limit their application in the field of foaming materials.
Carbon dioxide-based polyester-polycarbonate tetracopolymer (PPC-X) and n-pentane or isopentane are used as physical foaming agents to prepare high foaming ratio biodegradable foaming plastics under high pressure and high temperature conditions through the kettle press foaming method.
It achieves high foaming ratio (10-40 times), uniform and dense cell structure, good dimensional stability and certain flexibility and resilience, reducing costs and increasing the difficulty of industrial applications.
Smart Images

Figure CN119859385A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer foam materials, in particular to a biodegradable foam plastic and a preparation method thereof. Background Art
[0002] Foam is a lightweight material that is widely used in the cushioning and packaging industries due to its sound and heat insulation properties and damping performance. Most of the foams currently used and discarded (such as polystyrene foam and polyethylene foam, etc.) are non-biodegradable, causing serious environmental problems, so the urgency of developing biodegradable foams is increasing. However, most biodegradable polymers, such as the semi-crystalline polymer poly(lactic acid) (PLA), show low melt strength, resulting in low foaming ratios (less than 10 times) of the prepared foams, which not only cost much more than most polyethylene or polystyrene foams with foaming ratios of more than 30 times, but also have poor resilience.
[0003] In 2022, we used CO2 as a foaming agent and used the autoclave foaming method to prepare a non-brittle CO2-based polyester-polycarbonate (PPC-P) foam with a foaming ratio of 10-50 (Chinese patent CN 115651382A, Nanomaterials .2024, 14(13), 1120). The prepared PPC-P foam has uniform and dense pores. The disadvantage is that due to the low glass transition temperature (40~55℃) of PPC-P, it is easy to deform at high temperatures, so the dimensional stability of the obtained PPC-P foam is poor. At the same time, because the CO2 gas itself diffuses quickly in the foam, the foam is further prone to shrinkage. This greatly limits its application in the field of foaming materials. In 2024, we used phthalic anhydride, tetrachlorophthalic anhydride, propylene oxide and carbon dioxide to copolymerize to prepare a carbon dioxide-based polyester-polycarbonate tetrapolymer (PPC-X) (Chinese patent CN 118206728A). The prepared PPC-X has good light transmittance, high barrier properties, and a mechanical strength of up to 49MPa. T g The temperature is 69-75℃, which is higher than that of carbon dioxide-based polyester-polycarbonate (PPC-P). T g (40-55℃) has improved a lot. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and to prepare a biodegradable foam plastic using a carbon dioxide-based polyester-polycarbonate tetrapolymer (PPC-X) for the first time, thereby obtaining a biodegradable tetrapolymer foam plastic having a high foaming ratio, a relatively uniform and dense pore structure, and certain flexibility and resilience.
[0005] In order to achieve the above object, the present invention adopts the following technical solution: A biodegradable tetrapolymer foam plastic, comprising the following components in parts by weight: 88-95 parts of carbon dioxide based polyester-polycarbonate tetrapolymer, 5-12 parts of physical foaming agent; The physical foaming agent is one or both of n-pentane and isopentane; The carbon dioxide-based polyester-polycarbonate tetrapolymer (PPC-X) is a high molecular weight polymer obtained by tetrapolymerization of phthalic anhydride, tetrachlorophthalic anhydride, propylene oxide and carbon dioxide, and has a number average molecular weight of 50,000 to 150,000; its structure is shown in formula (1); wherein m≥1, n≥1, k≥0, j≥0; m, n, k and j are all integers;
[0006] Preferably, an organic filler is added to the above-mentioned biodegradable tetrapolymer foam plastic, and the added weight of the organic filler is 1-40% of the biodegradable tetrapolymer foam plastic.
[0007] Preferably, in the above-mentioned biodegradable tetrapolymer foam plastic, the organic filler is selected from one or more of corn starch, wheat starch, sweet potato starch and lignin fiber powder.
[0008] A method for preparing a biodegradable tetrapolymer foam plastic comprises the following steps: (1) using a wire extruder to pelletize carbon dioxide-based polyester-polycarbonate tetrapolymer strands to obtain micro-pellets; (2) placing the microparticles in a high-pressure reactor, first loading the dispersion medium, physical foaming agent and isolation agent, and then injecting N2, and obtaining homogeneous materials with different foaming agent adsorption contents by setting the saturation pressure, saturation time and saturation temperature in the reactor; (3) After the physical foaming agent is saturated with adsorption, the reactor is first cooled at low temperature and then slowly depressurized at low temperature. After the depressurization is completed, it is transferred to an analytical balance to confirm the adsorption amount of the physical foaming agent, and then transferred to a hot water bath for foaming. Subsequently, the foam beads after foaming are collected and a foam molded body is prepared by compression molding.
[0009] Preferably, in the above-mentioned method for preparing the biodegradable tetrapolymer foam plastic, the length / diameter ratio of the microparticles is 0.5-2, and the average weight of the microparticles is 0.1-20 mg.
[0010] Preferably, in the above-mentioned method for preparing the biodegradable tetrapolymer foam plastic, the saturation temperature is 75°C; the saturation pressure is 2.0MPa-5.0MPa; the saturation time is 6h-24h; and the temperature of the hot water bath is 55°C-85°C.
[0011] Preferably, in the above-mentioned method for preparing the biodegradable tetrapolymer foam plastic, the dispersion medium is deionized water, and the isolation agent is calcium phosphate.
[0012] Since the carbon dioxide-based polyester-polycarbonate tetrapolymer has a high glass transition temperature, after pentane is adsorbed under high temperature and high pressure conditions, the foaming agent n-pentane or isopentane can be stored in the material body, and foaming is carried out by increasing the temperature when used. This undoubtedly reduces the cost and the difficulty of industrial application. By adjusting the pressure during adsorption to 1.0MPa-2.0MPa, a foaming material with a foaming ratio of 10-40 times can be easily obtained, and it has a uniform and dense pore structure, and the obtained foam product is a non-brittle foam with certain flexibility and resilience. Under higher pressures, such as 3.0MPa-5.0MPa, the saturation time of n-pentane or isopentane in the polymer PPC-X will be greatly shortened, which can greatly improve the industrial efficiency.
[0013] Compared with the prior art, the present invention has the following beneficial effects: (1) In common EPS foaming, the selection principle of physical foaming agent is: pentane and PS have good compatibility. In the present invention, based on the structural characteristics of PPC-X, it is not difficult to find that the compatibility of pentane and PPC-X is general, but through designing experiments, we can achieve a higher adsorption amount of pentane in PPC-X particles (>7%). Although the compatibility of pentane and PPC-X is relatively general, unexpectedly, the foamed PPC-X has a high foaming ratio (10~45 times), a small pore size (~40μm), and a dense and uniform pore structure (the pore density can reach ~1.5×10 7 Cells / cm 3) and good foam dimensional stability and certain resilience. On the other hand, for most biodegradable polymers, the common physical foaming agent is CO2, and the fast desorption rate of CO2 gas limits their foaming behavior. Pre-foaming often occurs after the physical foaming agent is adsorbed, which significantly increases the requirements for the material foaming process and storage conditions. In the present invention, the desorption rate of the foaming agent n-pentane or isopentane in PPC-X is extremely low, which can achieve a good storage effect, which provides the possibility for long-term storage of foamed particles containing foaming agents. The present invention adopts a kettle pressure foaming method, uses n-pentane or isopentane as a foaming agent, has a saturation temperature of 75°C, adjusts the saturation pressure of the reactor to 1.0MPa-5.0MPa, and has a saturation time of 6h-24h, so as to obtain PPC-X foaming particles with a pentane adsorption amount greater than 7% and easy to store. When foaming in hot water at 60-80°C, PPC-X foaming beads with a foaming ratio of 10-40 can be easily obtained, and have a uniform and dense pore structure. The obtained PPC-X foam product is non-brittle foam with good flexibility.
[0014] (2) When n-pentane or isopentane is used as a physical foaming agent, its use is limited by its low solubility in biodegradable high molecular polymers. The present invention uses n-pentane or isopentane as a physical foaming agent through designed experiments, which can easily achieve an adsorption amount of the foaming agent in PPC-X greater than 7%, thereby obtaining a PPC-X foam material with a high foaming ratio. The foaming ratio of the biodegradable foam plastic of the present invention can exceed 40 times, which is a very high foaming ratio in the field of biodegradable plastic foaming, especially in the method of autoclave foaming.
[0015] (3) The polymer used in the present invention is synthesized from carbon dioxide, which utilizes greenhouse gas carbon dioxide, has the significance of carbon reduction, and is green and environmentally friendly.
[0016] (4) The biodegradable foam material prepared by the present invention has a high foaming ratio, a relatively uniform and dense pore structure, and has certain flexibility and resilience. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a scanning electron microscope image of a cross section of the foamed material obtained in Example 3 of the present invention; Figure 2 This is a scanning electron microscope image of the cross section of the foamed material obtained in Example 4 of the present invention. DETAILED DESCRIPTION Embodiment 1:
[0018] After drying the carbon dioxide-based polyester-polycarbonate tetrapolymer (PPC-X) in a vacuum drying oven at 80°C, the wire extruder was used to draw and pelletize. The temperature of zone 1 of the wire extruder was 145°C and the temperature of zone 2 was 160°C. Microparticles with a length / diameter ratio of 0.9-1.1 and an average weight of 1-3 mg were obtained. Then the microparticles with a mass m0 of 0.1086g were weighed and placed in a reactor. 45ml of deionized water, 5ml of n-pentane and 0.5g of calcium phosphate were added to the reactor. Then, N2 gas was used to pressurize the reactor to 1.5MPa. The saturation time was 24h, the saturation temperature was 75°C, and the magnetic stirring rate was 800rpm. After saturation, the reactor was cooled in a low-temperature ice water bath for 30 minutes, and the temperature in the reactor was kept below 10°C. Then, the pressure was slowly released at low temperature. After the pressure release was completed, the microparticles were collected and the surface moisture was wiped dry. They were transferred to an analytical balance to weigh the mass of PPC-X / n-pentane as m1: 0.1191g (calculated, the adsorption amount of n-pentane was 9.7%) and quickly transferred to a 60°C hot water bath for foaming experiments. After 1 minute, biodegradable foam beads were prepared, and foam moldings were prepared by compression molding. After testing, the prepared biodegradable foam plastic had a foaming ratio of 22 times, a pore size of 38μm, and a pore density of 1.5×10 7 Cells / cm 3 , the compression strength is 302kPa, the tensile strength is 930kPa, and the elongation at break is 216.3%.
[0019] Embodiment 2: After drying the carbon dioxide-based polyester-polycarbonate tetrapolymer (PPC-X) in a vacuum drying oven at 80°C, it was pelletized using a wire extruder. The temperature of zone 1 of the wire extruder was 145°C and the temperature of zone 2 was 160°C. Microparticles with a length / diameter ratio of 0.9-1.1 and an average weight of 1-3 mg were obtained. Then the microparticles with a mass m0 of 0.4396 g were weighed and placed in a reactor. 45 ml of deionized water, 5 ml of n-pentane and 0.5 g of calcium phosphate were added to the reactor. The reactor was then pressurized to 1.5 MPa using N2 gas. The saturation time was 24 h, the saturation temperature was 75°C, and the magnetic stirring rate was 800 rpm. After saturation, the reactor was cooled in a low-temperature ice water bath for 30 minutes, and the temperature in the reactor was kept below 10°C. Then, the pressure was slowly released at low temperature. After the pressure release was completed, the microparticles were collected and the surface moisture was wiped dry. The particles were transferred to an analytical balance to weigh the mass of PPC-X / n-pentane as m1: 0.4801g (calculated, the adsorption amount of n-pentane was 9.2%) and quickly transferred to a 70°C hot water bath for foaming experiments. After 1 minute, biodegradable foam beads were prepared, and foam moldings were prepared by compression molding. After testing, the prepared biodegradable foam plastic had a foaming ratio of 31 times, a pore size of 52μm, and a pore density of 1.1×10 7 Cells / cm 3 , the compression strength is 275kPa, the tensile strength is 620kPa, and the elongation at break is 157.6%.
[0020] Embodiment 3: After drying the carbon dioxide-based polyester-polycarbonate tetrapolymer (PPC-X) in a vacuum drying oven at 80°C, the wire extruder was used to draw and pelletize. The temperature of zone 1 of the wire extruder was 145°C and the temperature of zone 2 was 160°C. Microparticles with a length / diameter ratio of 0.9-1.1 and an average weight of 1-3 mg were obtained. Then the microparticles with a mass m0 of 0.2086g were weighed and placed in a reactor. 45 ml of deionized water, 5 ml of n-pentane and 0.5 g of calcium phosphate were added to the reactor. Then, N2 gas was used to pressurize the reactor to 2.5 MPa. The saturation time was 16h, the saturation temperature was 75°C, and the magnetic stirring rate was 800rpm. After saturation, the reactor was cooled in a low-temperature ice water bath for 30 minutes, and the temperature in the reactor was kept below 10°C. Then, the pressure was slowly released at low temperature. After the pressure release was completed, the microparticles were collected and the surface moisture was wiped dry. They were transferred to an analytical balance to weigh the mass of PPC-X / n-pentane as m1: 0.2309g (calculated, the adsorption amount of n-pentane was 10.7%) and quickly transferred to a 70°C hot water bath for foaming experiments. After 1 minute, biodegradable foam beads were prepared, and foam moldings were prepared by compression molding. After testing, the prepared biodegradable foam plastic had a foaming ratio of 36 times, a pore size of 55μm, and a pore density of 6.7×10 6 Cells / cm 3 , the compression strength is 256kPa, the tensile strength is 600kPa, and the elongation at break is 150.1%.
[0021] Embodiment 4: After drying the carbon dioxide-based polyester-polycarbonate tetrapolymer (PPC-X) in a vacuum drying oven at 80°C, it was pelletized using a wire extruder. The temperature of zone 1 of the wire extruder was 145°C and the temperature of zone 2 was 160°C. Microparticles with a length / diameter ratio of 0.9-1.1 and an average weight of 1-3 mg were obtained. Then the microparticles with a mass m0 of 0.3877 g were weighed and placed in a reactor. 45 ml of deionized water, 5 ml of n-pentane and 0.5 g of calcium phosphate were added to the reactor. Then, N2 gas was used to pressurize the reactor to 3.0 MPa. The saturation time was 12 h, the saturation temperature was 75°C, and the magnetic stirring rate was 800 rpm. After saturation, the reactor was cooled in a low-temperature ice water bath for 30 minutes, and the temperature in the reactor was kept below 10°C. Then, the pressure was slowly released at low temperature. After the pressure release was completed, the microparticles were collected and the surface moisture was wiped dry. They were transferred to an analytical balance to weigh the mass of PPC-X / n-pentane as m1: 0.4311g (calculated, the adsorption amount of n-pentane was 11.2%) and quickly transferred to a 70°C hot water bath for foaming experiments. After 1 minute, biodegradable foam beads were prepared, and foam moldings were prepared by compression molding. After testing, the prepared biodegradable foam plastic had a foaming ratio of 38 times, a pore size of 70μm, and a pore density of 6.2×10 6 Cells / cm 3 , the compression strength is 240kPa, the tensile strength is 571kPa, and the elongation at break is 146.7%.
[0022] Example 5 After drying the carbon dioxide-based polyester-polycarbonate tetrapolymer (PPC-X) in a vacuum drying oven at 80°C, the wire extruder was used to draw and pelletize the particles. The temperature of zone 1 of the wire extruder was 145°C and the temperature of zone 2 was 160°C. Microparticles with a length / diameter ratio of 0.9-1.1 and an average weight of 1-3 mg were obtained. The microparticles with a mass m0 of 0.7233 g were weighed and placed in a reactor. 45 ml of deionized water, 5 ml of n-pentane and 0.5 g of calcium phosphate were added to the reactor. The reactor was then pressurized to 3.5 MPa using N2 gas. The saturation time was 9 h, the saturation temperature was 75°C, and the magnetic stirring rate was 800 rpm. After saturation, the reactor was cooled in a low-temperature ice water bath for 30 min, and the temperature in the reactor was kept below 10°C. Then, the pressure was slowly released at low temperature. After the pressure release was completed, the microparticles were collected and the surface moisture was wiped dry. They were transferred to an analytical balance to weigh the mass of PPC-X / n-pentane as m1: 0.8101g (calculated, the adsorption amount of n-pentane was 12.0%) and quickly transferred to a 70°C hot water bath for foaming experiments. After 1 minute, biodegradable foam beads were prepared, and foam moldings were prepared by compression molding. After testing, the prepared biodegradable foam plastic had a foaming ratio of 42 times, a pore size of 29μm, and a pore density of 9.1×10 6 Cells / cm 3 , the compression strength is 291kPa, the tensile strength is 840kPa, and the elongation at break is 186.5%.
[0023] Example 6 After drying the carbon dioxide-based polyester-polycarbonate tetrapolymer (PPC-X) in a vacuum drying oven at 80°C, the wire extruder was used to draw and pelletize. The temperature of zone 1 of the wire extruder was 145°C and the temperature of zone 2 was 160°C. Microparticles with a length / diameter ratio of 0.9-1.1 and an average weight of 1-3 mg were obtained. Then the microparticles with a mass m0 of 0.2612g were weighed and placed in a reactor. 45ml of deionized water, 5ml of n-pentane and 0.5g of calcium phosphate were added to the reactor. Then, N2 gas was used to pressurize the reactor to 2.5MPa. The saturation time was 16h, the saturation temperature was 75°C, and the magnetic stirring rate was 800rpm. After saturation, the reactor was cooled in a low-temperature ice water bath for 30 minutes, and the temperature in the reactor was kept below 10 °C. Then, the pressure was slowly released at low temperature. After the pressure release was completed, the microparticles were collected and the surface moisture was wiped dry. They were transferred to an analytical balance to weigh the mass of PPC-X / n-pentane as m1: 0.2878g (calculated, the adsorption amount of n-pentane was 10.2%) and quickly transferred to a 75 °C hot water bath for foaming experiments. After 1 minute, biodegradable foam beads were prepared, and foam moldings were prepared by compression molding. After testing, the prepared biodegradable foam plastic had a foaming ratio of 26 times, a pore size of 44 μm, and a pore density of 1.3×10 7 Cells / cm 3 , the compression strength is 295kPa, the tensile strength is 896kPa, and the elongation at break is 202.2%.
[0024] Example 7 After drying the carbon dioxide-based polyester-polycarbonate tetrapolymer (PPC-X) in a vacuum drying oven at 80°C, the wire extruder was used to draw and pelletize. The temperature of zone 1 of the wire extruder was 145°C and the temperature of zone 2 was 160°C. Microparticles with a length / diameter ratio of 0.9-1.1 and an average weight of 1-3 mg were obtained. Then the microparticles with a mass m0 of 0.1357g were weighed and placed in a reactor. 45ml of deionized water, 5ml of isopentane and 0.5g of calcium phosphate were added to the reactor. Then, N2 gas was used to pressurize the reactor to 1.5MPa. The saturation time was 24h, the saturation temperature was 75°C, and the magnetic stirring rate was 800rpm. After saturation, the reactor was cooled in a low-temperature ice water bath for 30 minutes, and the temperature in the reactor was kept below 10°C. Then, the pressure was slowly released at low temperature. After the pressure release was completed, the microparticles were collected and the surface moisture was wiped dry. The microparticles were transferred to an analytical balance to weigh the mass of PPC-X / isopentane as m1: 0.1468g (the isopentane adsorption amount was calculated to be 8.2%) and quickly transferred to a 75°C hot water bath for foaming experiments. After 1 minute, biodegradable foam beads were prepared, and foam moldings were prepared by compression molding. After testing, the prepared biodegradable foam plastic had a foaming ratio of 25 times, a pore size of 40μm, and a pore density of 1.4×10 7 Cells / cm 3 , the compression strength is 285kPa, the tensile strength is 876kPa, and the elongation at break is 207.9%.
[0025] Example 8 After drying the carbon dioxide-based polyester-polycarbonate tetrapolymer (PPC-X) in a vacuum drying oven at 80°C, the wire extruder was used to draw and pelletize the particles. The temperature of zone 1 of the wire extruder was 145°C and the temperature of zone 2 was 160°C. Microparticles with a length / diameter ratio of 0.9-1.1 and an average weight of 1-3 mg were obtained. Then the microparticles with a mass m0 of 0.2534 g were weighed and placed in a reactor. 45 ml of deionized water, 5 ml of isopentane and 0.5 g of calcium phosphate were added to the reactor. Then, N2 gas was used to pressurize the reactor to 2.5 MPa. The saturation time was 16 h, the saturation temperature was 75°C, and the magnetic stirring rate was 800 rpm. After saturation, the reactor was cooled in a low-temperature ice water bath for 30 minutes, and the temperature in the reactor was kept below 10°C. Then, the pressure was slowly released at low temperature. After the pressure release was completed, the microparticles were collected and the surface moisture was wiped dry. They were transferred to an analytical balance to weigh the mass of PPC-X / isopentane as m1: 0.2820g (the isopentane adsorption amount was calculated to be 11.3%) and quickly transferred to a 75°C hot water bath for foaming experiments. After 1 minute, biodegradable foam beads were prepared, and foam moldings were prepared by compression molding. After testing, the prepared biodegradable foam plastic had a foaming ratio of 28 times, a pore size of 51μm, and a pore density of 1.2×10 7 Cells / cm 3 , the compression strength is 307kPa, the tensile strength is 918kPa, and the elongation at break is 206.1%.
[0026] Example 9 By weight, 80 parts of carbon dioxide-based polyester-polycarbonate tetrapolymer and 20 parts of cassava starch were blended in a torque blender for 10 minutes at 150°C and 60rpm to obtain a blended composite material. After the carbon dioxide-based polyester-polycarbonate blended composite material was dried in a vacuum drying oven at 80°C, it was pelletized using a wire extruder. The temperature of zone 1 of the wire extruder was 145°C and the temperature of zone 2 was 160°C to obtain microparticles with a length / diameter ratio of 0.9-1.1 and an average weight of 1-3mg. Then weigh the microparticles with a mass m0 of 0.4258g, place the microparticles in a reactor, add 45ml of deionized water, 5ml of n-pentane and 0.5g of calcium phosphate to the reactor, and then pressurize to 3.0MPa with N2 gas. The saturation time was 12h, the saturation temperature was 75°C, and the magnetic stirring rate was 800rpm. After saturation, the reactor was cooled in a low-temperature ice water bath for 30 minutes, and the temperature in the reactor was kept below 10°C. Then, the pressure was slowly released at low temperature. After the pressure release was completed, the microparticles were collected and the surface moisture was wiped dry. The microparticles were transferred to an analytical balance to weigh the mass of PPC-X / n-pentane as m1: 0.4556g (calculated, the adsorption amount of n-pentane was 7.0%) and quickly transferred to a 70°C hot water bath for foaming experiments. After 1 minute, biodegradable foam beads were prepared, and foam moldings were prepared by compression molding. After testing, the prepared biodegradable foam plastic had a foaming ratio of 20 times, a pore size of 90μm, and a pore density of 9.2×10 6 Cells / cm 3 , the compression strength is 330 kPa, the tensile strength is 923 kPa, and the elongation at break is 204.7%.
[0027] Comparative Example 1 10 phr of 4,4'-oxybisbenzenesulfonyl hydrazide (OBSH blowing agent) and carbon dioxide-based polyester-polycarbonate tetrapolymer were blended in a torque blender for 10 min at 150° C. and 60 rpm to obtain a blended polymer.
[0028] The blended polymer was then pelletized using a wire extruder. The temperature of zone 1 of the wire extruder was 145°C and the temperature of zone 2 was 160°C. Microparticles with a length / diameter ratio of 0.9-1.1 and an average weight of 1-3 mg were obtained. 0.1053 g of microparticles were weighed and placed in a blast oven at 180°C for 20 minutes to obtain biodegradable PPC-X foam beads. The foamed body was prepared by compression molding. After testing, the prepared biodegradable foam plastic had a foaming ratio of 10 times, a cell size of 159 μm, and a cell density of 3.0×10 6 Cells / cm 3, the compression strength is 127kPa, the tensile strength is 357kPa, and the elongation at break is 93.3%.
[0029] It can be seen that the present invention can achieve an adsorption amount of more than 7% of the physical foaming agent (n-pentane or isopentane) in the high molecular polymer PPC-X by the autoclave foaming method, that is, under high pressure and high temperature conditions, and the foaming agent is well stored in PPC-X. And by adjusting different saturation pressures, saturation times, and foaming temperatures, etc., a biodegradable foam plastic with a high foaming ratio can be prepared, and the obtained foam plastic has certain flexibility and resilience.
Claims
1. A biodegradable tetrapolymer foam plastic, characterized in that: The following components are included in the formula: composition: 88-95 parts of carbon dioxide based polyester-polycarbonate tetrapolymer, 5-12 parts of physical foaming agent; The physical foaming agent is one or both of n-pentane and isopentane; The carbon dioxide-based polyester-polycarbonate quaternary copolymer is a high molecular weight polymer obtained by quaternary copolymerization of phthalic anhydride, tetrachlorophthalic anhydride, propylene oxide and carbon dioxide, and has a number average molecular weight of 50,000 to 150,000; its structure is shown in formula (1); wherein m≥1, n≥1, k≥0, j≥0; m, n, k and j are all integers; 。 2. The biodegradable tetrapolymer foam according to claim 1, characterized in that: An organic filler is also added, and the added weight of the organic filler is 1-40% of the biodegradable tetrapolymer foam plastic.
3. The biodegradable tetrapolymer foam according to claim 2, characterized in that: The organic filler is selected from one or more of corn starch, wheat starch, sweet potato starch and lignin fiber powder.
4. A method for preparing the biodegradable tetrapolymer foam plastic according to claim 1, characterized in that: The steps include: (1) using a wire extruder to pelletize carbon dioxide-based polyester-polycarbonate tetrapolymer strands to obtain micro-pellets; (2) placing the microparticles in a high-pressure reactor, first loading the dispersion medium, physical foaming agent and isolation agent, and then injecting N2, and obtaining homogeneous materials with different foaming agent adsorption contents by setting the saturation pressure, saturation time and saturation temperature in the reactor; (3) After the physical foaming agent is saturated with adsorption, the reactor is first cooled at low temperature and then slowly depressurized at low temperature. After the depressurization is completed, it is transferred to an analytical balance to confirm the adsorption amount of the physical foaming agent, and then transferred to a hot water bath for foaming. Subsequently, the foam beads after foaming are collected and a foam molded body is prepared by compression molding.
5. The method for preparing the biodegradable tetrapolymer foam plastic according to claim 4, characterized in that: The length / diameter ratio of the microparticles is 0.5-2, and the average weight of the microparticles is 0.1-20 mg.
6. The method for preparing the biodegradable tetrapolymer foam plastic according to claim 4, characterized in that: The saturation temperature is 75°C; the saturation pressure is 2.0MPa-5.0MPa; the saturation time is 6h-24h; and the temperature of the hot water bath is 55°C-85°C.
7. The method for preparing the biodegradable tetrapolymer foam plastic according to claim 4, characterized in that: The dispersion medium is deionized water, and the isolation agent is calcium phosphate.
Citation Information
Patent Citations
Phthalic anhydride / tetrachlorophthalic anhydride / epoxide / carbon dioxide quadripolymer and preparation method thereof
CN118206728A
Biodegradable foamed plastic and preparation method thereof
CN115651382A
Temperature-resistant degradable foam material
CN116426100A
Fruit net cover and preparation method thereof
CN116875023A
High-heat-resistance and high-magnification biodegradable foamed plastic and preparation method thereof
CN117624865A